miR-181a initiates and perpetuates oncogenic transformation through the regulation of innate immune signaling - Matthew Knarr (Nature Portfolio, 2020)
The majority of high grade serous ovarian cancers originate from fallopian tube secretory epithelial cells (FTSECs). Here the authors show that miR-181a drives oncogenic transformation in FTSECs through the cooperative inhibition of the tumor suppressor RB1 and of STING, resulting in genomic instability and suppression of intrinsic interferon signaling.